Sexual vulnerability of migrant women in the multicultural context of French Guiana: A societal issue - Alcouffe, Leslie; Huber, Florence; Creton, Pierre-Marie; Bitan, Luana; Gonzalez, Adriana; Volpellier, Muriel; Panfili, Biancaelena; Adenis, Antoine; Vignier, Nicolas (Frontiers in Public Health, 2022)
Background French Guiana is a multicultural French territory in Amazonia with an old migration history and a high prevalence of HIV infection. The objective of this study was to evaluate situations of sexual vulnerability and their associated factors among migrant women in French Guiana. Methods A cross-sectional epidemiological study was carried out in 2021 in the French Red Cross Prevention and Health Centers of the two main cities of French Guiana (Cayenne and Saint Laurent du Maroni). Analysis was performed with multivariate stepwise logistic regression using Stata 15.0 software. Findings A total of 382 migrant women were included, with a median age of 31 years, mainly born in Haiti (80%), Suriname (9%), or Dominican Republic (6%), undocumented (71%), and with financial difficulties (77%). Among the 20% having casual partners, 57% reported unprotected sexual intercourse, more often the Haitian and Surinamese women. A history of rape was reported by 20% of women, most often in the country of origin (71%). Lifetime rape was associated with being threatened [aOR = 3.69 (1.96–6.96)] or being physically abused [aOR = 12.95 (6.51–25.75)] in the multivariate analysis. Among the women surveyed, 30% reported having ever exchanged sex for money, food, or shelter in their lifetime. Transactional sex is more common among Dominican women [aOR = 5.59 (1.84–16.95)] and women living in French Guiana for more than 2 years [aOR = 2.32 (1.38–3.92)]. Transactional sex is also associated with alcohol misuse [aOR = 2.57 (1.46–4.53)], history of threats [aOR = 2.03 (1.14–3.63)], history of rape [aOR = 1.92 (1.03–3.60)], and depressive disorders [aOR = 2.08 (1.21–3.60)]. Interpretation Migrant women in French Guiana are in a situation of sexual vulnerability. An intervention focused on sexual education and the promotion of prevention tools among Haitian women is advisable. Better prevention and support for transactional sex are needed to prevent violence and its mental health and alcohol misuse consequences for all women, especially Dominican women.